My Shepherd, though you do not know me: the Persian royal propaganda model in the Nehemiah Memoir - Schulte, Lucas L. (Contributions to biblical exegesis and theology, 2016)
The redactional history of the book of Nehemiah is a hotly debated topic within scholarship. While a general consensus both attributes Neh. 1:1-2:20; 4:1-7:5; and 13:4-31 to the Nehemiah Memoir and postulates the influence of ancient Near Eastern royal inscriptions, previous scholarship lacks a systematic examination of Persian-period royal inscriptions in discussing the redactional history of Nehemiah. This present book examines Persian-period inscriptions from Judah's neighbors, Babylonia and Egypt, and identifies a propaganda model in which Persian kings are supported by the local deities and are heirs to the local dynasties. This propaganda model resembles depictions of Artaxerxes in sections of Nehemiah often attributed to the Memoir. Challenging a recent trend attributing religious references to Hellenistic redactions, this study finds that references in Nehemiah to divine authorization of Artaxerxes akin to the royal propaganda model in Persian-period texts from Babylon and Egypt most likely date to the Persian-period Nehemiah Memoir due to a shared literary context